(untitled) (Philologia, 2021)
This paper demonstrates the approach to the study of primary school textbooks gender analysis and its results. The results explicitly tell us how women have been marginalized as text and image authors in the analyzed textbooks. Female characters in textbooks are also less looked at and compared to male characters, although both have been interpreted in traditional and stereotypical manner (family and professional roles, values and interests…) as a part of text worlds. Stereotypes are partially obliterated only when presenting characters’ outlook. Aiming to ensure the notions of textbooks as a part of the important role in promoting policy of gender equality and correspond to the concept of a contemporary textbook, crucial findings suggest that educational policy creators are to be concerned about the textbook accreditation standards and gender equality obtainment, as well as about setting up conditions for introducing the gender aspect in the educational system.